Fungi as a Potential Source of Pigments: Harnessing Filamentous Fungi - Kalra, Rishu; Conlan, Xavier A.; Goel, Mayurika (Frontiers in Chemistry, 2020)
The growing concern over the harmful effects of synthetic colorants on both the consumer and the environment has raised a strong interest in natural colouring alternatives. As a result the worldwide demand for colourants of natural origin is rapidly increasing in the food, cosmetic and textile sectors. Natural colourants have the capacity to be used for a variety of industrial applications, for instance, as dyes for textile and non-textile substrates such as leather, paper, within paints and coatings, in cosmetics, and in food additives. Currently, pigments and colourants produced through plants and microbes are the primary source exploited by modern industries. Among the other non-conventional sources, filamentous fungi particularly ascomycetous and basidiomycetous fungi (mushrooms), and lichens (symbiotic association of a fungus with a green alga or cyanobacterium) are known to produce an extraordinary range of colours including several chemical classes of pigments such as melanins, azaphilones, flavins, phenazines, and quinines. This review seeks to emphasise the opportunity afforded by pigments naturally found in fungi as a viable green alternative to current sources. This review presents a comprehensive discussion on the capacity of fungal resources such as endophytes, halophytes, and fungi obtained from a range or sources such as soil, sediments, mangroves and marine environments. A key driver of the interest in fungi as a source of pigments stems from environmental factors and discussion here will extend on the advancement of greener extraction techniques used for the extraction of intracellular and extracellular pigments. The search for compounds of interest requires a multidisciplinary approach and techniques such as metabolomics, metabolic engineering and biotechnological approaches that have potential to deal with various challenges faced by pigment industry